Health Policies Under The Special Autonomy Regime : An Evaluation Using Health Indicators - Andhika Theodora Suratman (Jurnal Administrasi Publik, 2014)
Indonesian Law No.21/2001 on Special Autonomy regulates special autonomy given to the Province of Papua. Articles 59 and 60 of the law articulates the obligations of the provincial government to provide quality health care, prevent and manage endemic and life-threatening diseases, and improve the nutritional status of the people of Papua in cooperation with religious organizations, non-governmental organizations (NGOs) and other qualified establishments. This study intends to evaluate health policies under the special autonomy law and its effects towards health indicators such as doctor to patient ratio, number of health facilities, infectious diseases, nutritional status and health programs including antenatal care, vaccination, birth planning and labor assisted by health professionals by collecting and examining statistics on the topics above.It reveals that budget allocated for health purposes is significantly increase from IDR 87,239,000,000 in 2002 (15.9% from total allocated budget) to 33,7% (862,383,000,000) in 2006 and has been utilized to improve health facilities both in quality and quantity.Wide range available secondary data are used and analyzed. It is concluded that, physical health infrastructure were built across the provinces. however, the implementation of health policies under the 2001 Special Autonomy Law does not translate into satisfying results using known health indicators.Keywords: special autonomy, health budget, health indicators, Papua.